Wolfram syndrome 2 gene (CISD2) deficiency disrupts Ca2+-mediated insulin secretion in β-cells - Zhao-Qing Shen; Wen-Tai Chiu; Cheng-Heng Kao; Yu-Chen Chen; Li-Hsien Chen; Tsai-Wen Teng; Shao-Yu Hsiung; Tsai-Yu Tzeng; Chien-Yi Tung; Chi-Chang Juan; Ting-Fen Tsai (Molecular Metabolism)
Objective: Diabetes, characterized by childhood-onset, autoantibody-negativity and insulin-deficiency, is a major manifestation of Wolfram syndrome 2 (WFS2), which is caused by recessive mutations of CISD2. Nevertheless, the mechanism underlying β-cell dysfunction in WFS2 remains elusive. Here we delineate the essential role of CISD2 in β-cells. Methods: We use β-cell specific Cisd2 knockout (Cisd2KO) mice, a CRISPR-mediated Cisd2KO MIN6 β-cell line and transcriptomic analysis. Results: Four findings are pinpointed. Firstly, β-cell specific Cisd2KO in mice disrupts systemic glucose homeostasis via impairing β-granules synthesis and insulin secretion; hypertrophy of the β-islets and the presence of a loss of identity that affects certain β-cells. Secondly, Cisd2 deficiency leads to impairment of glucose-induced extracellular Ca2+ influx, which compromises Ca2+-mediated insulin secretory signaling, causing mitochondrial dysfunction and, thereby impairing insulin secretion in the MIN6-Cisd2KO β-cells. Thirdly, transcriptomic analysis of β-islets reveals that Cisd2 modulates proteostasis and ER stress, mitochondrial function, insulin secretion and vesicle transport. Finally, the activated state of two potential upstream regulators, Glis3 and Hnf1a, is significantly suppressed under Cisd2 deficiency; notably, their downstream target genes are deeply involved in β-cell function and identity. Conclusions: These findings provide mechanistic insights and form a basis for developing therapeutics for the effective treatment of diabetes in WFS2 patients.